Association of placenta previa with placental size in Japanese women: A study from a single tertiary referral center. Issue 2 (2nd December 2021) - Kyozuka, Hyo; Jin, Toki; Fujimori, Mimori; Matsuno, Mariko; Nomura, Shinji; Suzuki, Daisuke; Fukuda, Toma; Murata, Tsuyoshi; Yasuda, Shun; Yamaguchi, Akiko; Nomura, Yasuhisa; Fujimori, Keiya
Abstract: Aim: The effect of placenta previa on age‐specific placental size has not yet been elucidated. This study aimed to examine the effect of placenta previa on the Japanese standardized z‐scores of placental size. Methods: This retrospective cohort study included Japanese participants from Ohta Nishinouchi Hospital with single pregnancies who gave birth during 2013–2019. The participants were categorized into two groups based on the presence or absence of placenta previa. Multiple linear regression analyses were used to identify the association of placenta previa with the z‐score of placental size, after adjusting for factors, such as maternal smoking status, maternal age, assisted reproductive technology, myoma uteri, uterine anomaly, maternal hypertension at the time of pregnancy, and body mass index before pregnancy. Results: A total of 4071 Japanese women (76 with placenta previa and 3995 without placenta previa) were identified. Placenta previa significantly increased the placental weight z‐score (partial regression coefficient: 0.44, 95% confidence interval 0.10–0.70, p  < 0.001). Conclusion: Placenta previa increased the age‐specific placental size. Further studies are required to examine whether placenta previa is associated with the risk of obstetrics complications related to the placental size.